Medical Nutrition Therapy - Bhattarai, Jyoti (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Diabetes can lead to devastating expensive complications such as eye blindness, heart disease, stroke, leg amputation etc. To prevent such complications of diabetes it is really important that health care workers including patients understand the ways of improving or reducing the chances of developing such complications. It has been proven that proper management of diabetes early on can reduce such expensive and painful complications.